AI-driven Personal Remote Sensing Smartwatch for Respiratory and Environmental Health Assessment and Personalized Insights - Kassem, Reem (2025)
In an era where advanced technology prevails, artificial intelligence (AI) has revolutionized health monitoring practices. This paper presents the development and implementation of a novel smartwatch designed to monitor both physiological and environmental parameters. The watch measures vital body values such as heart rate and blood oxygen saturation levels, and upon detecting any irregularities, it assesses environmental factors such as temperature, humidity, and the levels of different gases in the air. The correlation between health irregularities and environmental parameters is done through the integration of AI, providing the user with personalized health insights and recommendations. The results demonstrate that the device functions effectively, showcasing its capability for real-time monitoring and early detection. This paper goes into detail about the purpose, design, functionality, applications, and future works of our smartwatch, highlighting its significance in health monitoring.